Highschool Student Engagement in Active Learning Classrooms - Mareike Seska Diana Lotulung (Journal on Education, 2023)
This descriptive analytical on-going study examines the engagement of the Indonesian high school students as they participated in the classroom activity, particularly in whole class discussion settings. The engagement is investigated in three measures, the word count, unprovoked student talk and turn count. While the focus is on student talk, teacher talk will also be measured with the purpose of examining the interaction and to serve as a comparison to the measures of the student talk. The participants will be 380 students of grade 10-12 who enrolled in a private High School. Data was extracted from the recording of 30 meeting sessions. The engagement was ascertained based on an analysis of transcripts from the classroom observation. And from these transcripts, the three the measures of engagement, word count, unprovoked student talk and turn count were counted. The findings of this study were the ratio of 5:1 classroom talk where the teacher dominated the classroom talk, and the low engagement in terms of unprovoked student talk and turn count in the whole class lecture and discussion settings. Recommendation on classroom procedure was provided.